Psychological distance and efficacy: analyzing the framing of climate change on US agricultural news websites using LLM-assisted content analysis - Li, Wenzhu; Shanahan, James; Liu, Yingcui (Frontiers in Communication, 2026)
Agriculture has significantly contributed to overall greenhouse gas emissions. Farmers’ perceptions of climate change play a critical role in shaping their attitudes toward adopting sustainable agricultural practices. News media play a crucial role in shaping public awareness and perceptions of climate change, which in turn may influence people’s behavior. Agricultural media serve as an important source of information for agricultural practices. However, there is limited research focusing on agricultural media and its potential relation to farmer practices. This study aims to address these gaps by applying a Large Language Model-assisted Content Analysis method to analyze climate change-related articles published between 2014 and 2023, across three US agricultural news websites. The findings indicate that agricultural media frequently use efficacy-related frames to discuss climate change. Rather than engaging in political or scientific debates, these outlets focus on information that is directly applicable and relevant to farming practices. Additionally, agricultural media may mitigate psychological distance in the reader (the farmer) by emphasizing immediate climate change risks, and addressing local concerns.